Factors of networked economy development in Ukraine: economic and legal context - Pushak, Ya.; Kravchuk, I.; Makeieva, O. (Економічний вісник Донбасу, 2018)
Under the influence of information technology, the features and content of organization forms of economy change; new kinds of production and forms of doing business are created, a main base of functioning networked economy is formed. The expanding of network approach for organization of economic relationships creates real changes in market and competitive structures, requires a necessity of changing aims and methods of entrepreneurship. The issues of networked economy forming and development were studied by both foreign researchers (J. Galbraith, A. Toffler, P. Druker) and native scholars (V. Bazylevych, V. Heyets, I. Besedina). The whole imagination about the process of networked economy forming is impossible without learning the factors, which define it, with taking in count specificity of native market environment, which is not researched enough in the national scientific field. Research of the factors of networked economy development based on analysis of international indexes of information environment development; determination of threats of information security in doing business. The analysis of advantageous and deterring factors of expanding network approach in doing business is carried out, the disadvantages of its law providing are defined, a forecast of Ukraine’s networked readiness is constructed. The threats of expanding network economy in business and society are explained. The main factors, which prevent development of ІCТ in Ukraine’s economy, are the low rate of adoption them by government, business; the low rate in law securing of network economy. Following the criteria of information security in network economy facilitates stabilization in relationships towards market’s stakeholders and will become one of the main parts in business development. Статтю присвячено дослідженню факторів розвитку вітчизняної мережевої економіки на основі аналізу міжнародних індексів розвитку інформаційного середовища; обґрунтуванню загроз інформаційної безпеки ведення бізнесу. Проведено аналіз сприятливих та гальмуючих факторів поширення мережевого підходу до ведення бізнесу, здійснено SWOT-аналіз інфраструктури та регуляторного середовища готовності участі підприємств у мережевій економіці, визначено недоліки її нормативно-правового забезпечення, побудовано прогноз мережевої готовності України. Обґрунтовано загрози поширення мережевої економіки в бізнесі і у суспільстві. Основними факторами, що стримують розвиток ІКТ в економіці України, є: невисокий рівень їх освоєння урядом, бізнесом; недостатнє законодавче забезпечення мережевої економіки. Статья посвящена исследованию факторов развития сетевой экономики на основе анализа международных индексов развития информационной среды; обоснованию угроз информационной безопасности ведения бизнеса. Проведен анализ благоприятных и тормозящих факторов распространения сетевого подхода к ведению бизнеса, осуществлен SWOT-анализ инфраструктуры и регуляторной среды готовности участия предприятий в сетевой экономике, определены недостатки ее нормативно-правового обеспечения, построен прогноз сетевой готовности Украины. Обоснованы угрозы распространения сетевой экономики в бизнесе и в обществе. Основными факторами, сдерживающими развитие ИКТ в экономике Украины, являются: невысокий уровень их использования правительством, бизнесом; недостаточное законодательное обеспечение сетевой экономики.